The Use of Action Research in Marketing Strategy Development. - Maklan, Stan; Knox, Simon; Ryals, Lynette (Cranfield University, 2008)
One of the key roles of market research has been to help reduce risk in marketing strategy development. However, traditional market research is in danger of being left behind by new practices in Sales, Marketing, and Business Development. Reflecting an increasingly participative approach to employee and customer relationships, these disciplines are moving towards greater involvement of front line staff and customers in the co-creation of value for companies. The authors illustrate how Action Research can provide tools and methods by which market researchers can assist and improve this co-creation process for both commercial and not-for-profit organisations. The implications for market researchers and research practices in strategy development are identified.
Keywords: Action Research; Marketing Strategy Development; Case Study Analysis